Integrating Lampung Local Wisdom into Science Education: Development and Validation of a Culturally Responsive Textbook to Enhance Physics Learning Outcomes - Rosa, Friska Octavia; Arif Rahman Aththibby; Adya Rosa Prasasti; Sukmanah Chomsun; Estika Prameswari (Jurnal Pendidikan Fisika, 2025)
The consistently low national performance in science, particularly at the junior high level, highlights the urgent need for innovative approaches in Indonesian science education. Despite policy reforms such as the Indonesian Merdeka Curriculum, many science learning experiences remain abstract and disconnected from students’ daily lives, leading to low motivation and achievement. To address this gap, this study aimed to develop a science textbook model grounded in Lampung local wisdom to create more meaningful, contextualized, and engaging learning experiences. Employing a Research and Development (R&D) design, the study followed the ADDIE framework, which consists of the steps analyze, design, develop, implement, and evaluate. 30 eight-grade students at SMP Negeri 3 Batanghari, East Lampung, participated in a one-group pretest–posttest design. Validation by two science education experts rated the textbook as “very good,” confirming the product’s quality and curricular relevance. Statistical analysis revealed a significant improvement in learning outcomes, with a mean gain of 10.46 points and a significance value of 0.000, while classroom observations indicated increased engagement, enthusiasm, and cultural pride. The novelty of this study lies in the systematic mapping of Lampung’s cultural practices directly onto science concepts, such as tapis weaving, traditional games, and piil pesenggiri values, thereby bridging the gap between scientific knowledge and cultural identity. In conclusion, the research demonstrates that integrating local wisdom into science education enhances both learning achievement and cultural relevance. This study contributes to the field of physics education by providing empirical evidence and a replicable framework for a culturally responsive science curriculum, and offers significant implications for teachers, curriculum developers, and policymakers.